Differential modulation of platelet adhesion and spreading by adhesive ligand density - Zarka, Revital; Spatz, Joachim P. (Nano letters, 2019)
Platelets play a major role in hemostasis and thrombosis, by binding to the underlying extracellular matrix around injured blood vessels, via integrin receptors. In this study, we investigated the effects of adhesive ligand spacing on the stability of platelets’ adhesion and the mode of their spreading on extracellular surfaces. Toward this end, we have examined the differential adhesion and spreading of human platelets onto nanogold-patterned surfaces, functionalized with the αIIbβ3 integrin ligand, SN528. Combining light- and scanning electron-microscopy, we found that interaction of platelets with surfaces coated with SN528 at spacing of 30-60 nm induces the extension of filopodia through which the platelets stably attach to the nanopatterned surface and spread on it. Increasing the nanopattern-gold spacing to 80-100 nm resulted in a dramatic reduction (>95%) in the number of adhering platelets. Surprisingly, a further increase in ligand spacing to 120 nm resulted in platelet binding to the surface at substantially larger numbers, yet these platelets remained discoid and were essentially devoid of filopodia and lamellipodia. These results indicate that the stimulation of filopodia extension by adhering platelets, and the consequent spreading on these surfaces depend on different ligand densities. Thus, the extension of filopodia occurs on surfaces with a ligand spacing of 100 nm or less, while the sustainability and growth of these initial adhesions and induction of extensive platelet adhesion and spreading requires lower ligand-to-ligand spacing (≤60 nm). The mechanisms underlying this differential ligand-density sensing by platelets, as well as the unexpected retention of discoid platelets on surfaces with even larger spacing (120 nm) are discussed.
Gesehen am 16.07.2019